A qualitative study on a novel peer collaboration care programme during the first COVID‐19 outbreak: A SWOT analysis - Carmen Baez‐Leon; Domingo Palacios‐Ceña; Cesar Fernandez‐de‐las‐Peñas; Juan Francisco Velarde‐García; Mª Ángeles Rodríguez‐Martínez; Patricia Arribas‐Cobo (Wiley, 2022)
Abstract The pandemic has forced nursing teams to incorporate new programmes that modify the organization of care and the use of material resources. Aims The purpose of this study was to describe the perspectives of the nursing team about the strengths/opportunities and weaknesses/threats of a novel peer collaboration care programme during the first outbreak of the pandemic. Design A qualitative case study with focus groups was conducted in June 2020. Methods We included 23 participants (seven nurses, seven assistant nursing care technicians and nine charge nurses). Thematic and strengths/opportunities and weaknesses/threats analysis were performed. Results The strengths of the peer collaboration care programme are the optimization of care and protective equipment. Its weaknesses are that veteran nurses carry the entire burden, and the lack of personal protective equipment makes it difficult to implement the peer collaboration care programme. Finally, misinformation, lack of facilities and time to teach the peer collaboration care programme are considered threats. Conclusion This strengths/opportunities and weaknesses/threats analysis has led to a comprehensive new project to improve the nursing care. Impact The incorporation of the peer collaboration care programme contributed to the development of new organizational and management programmes for the COVID‐19 pandemic. This study has gave empirical evidence to nurses and care managers to optimize and organize care, work, human and material resources during the pandemic.